Family Policies and Early Childhood education and care in France: An Exploratory Study - Callet-Venezia, Ingrid (Formazione & insegnamento, 2026)
Family support policies in France are characterized, on the one hand, by the concept of “free choice” for parents with children under three years of age, along with a diversification of service provision, which has enabled the country to meet the objectives set out in the Barcelona agreements; on the other hand, they focus on combating social inequalities through early schooling and compulsory education starting at age three. This paper aims to analyse educational and family policies in France and presents an exploratory study investigating early childhood professionals’ perceptions of the role of childcare centres (crèches), comparing them with policy choices.